Case files. Obstetrics & Gynecology - Toy, Eugene C. (New York : McGraw-Hill Medical, 2013)
"Sixty high-yield obstetrics and gynecoloy cases help you sharpen your diagnostic and problem-solving skills. You need exposure to high-yield cases to excel on the obstetrics and gynecology clerkship and the shelf-exam. Case Files: Obstetrics and Gynecoloy presents sixty real-life cases that illustrate essential concepts. Each case includes complete discussion, clinical pearls, references, definitions of key terms, and USMLE-style review questions with detailed explanations of the correct answers. With this system, you'll learn in the context of real patients, rather than merely memorize facts"--Provided by publisher.
Keywords: Gynecology -- Case Reports; Gynecology -- Examination Questions; Obstetrics -- Case Reports; Obstetrics -- Examination Questions